Internal customer satisfaction towards HRM practices and its influence on external customers and organisational outcomes - Wok, Saodah; Hashim, Junaidah (2011)
This study measures the internal customer satisfaction towards HRM practices and its relationship with external customer satisfaction and with other organisational outcomes such as job satisfaction, employee commitment, and turnover intention. This study is unique because it examines the internal customer satisfaction, particularly towards one of the most important management aspects such as HRM practices. It uses the customers‟ satisfaction framework instead of job satisfaction framework. Data was collected from five universities in the Klang Valley. Data was collected from internal customers (employees) and external customers (students). There were 575 internal customers and 600 external customers participated in this study. The findings revealed that employees are satisfied with the HRM practices of their organisation. This study partially supports the hypothesis that internal customers‟ satisfaction is positively related to external customers‟ satisfaction whereby the students are satisfied with the academic staff, provided the academic staff members are given opportunity for career development and they receive good facilities and services for their well-being. The findings further revealed that external customers‟ satisfaction with administrative staff members, are very much affected by the HRM practices, except for selection. The relationships between turnover intention and HRM practices are rather low, yet significant except for recruitment which is found to be not significant. This study also found that turnover intention is positively related to HRM practices. This means that despite their satisfaction with the HRM practices, the employees have the intention of quitting their job for a better offer. The implications are discussed.